FAPE Model of Exceptional Student Education Leadership - Dubberly, Russell G. (Journal of the American Academy of Special Education Professionals, 2012)
The FAPE Model of Exceptional Education Leadership is defined as facilitative, affiliative, praising and rewarding, and experiential and empirical. The FAPE administrator uses a facilitative approach that guides and coaches to help employees find a pathway to success. This leader works to build emotional capacity between all members of the educational organization and is seen as accessible. The FAPE administrator recognizes and praises staff for their accomplishments and is a support for all employees. Finally, the FAPE administrator does not "go it alone", but uses the resources of all staff and faculty and connects all instruction and curricular choices to empirical research.